Evaluasi Mutu Pelayanan Kesehatan Terhadap Kepuasan Pasien Di Instalasi Rawat Inap RS Imelda Pekerja Indonesia Medan - Issumi Maharani Tanjung; Thomson Nadapdap; Iman Muhammad (Pusat Riset dan Inovasi Nasional, 2023)
Hospitals are an integral part of social and media organizations whose function is to provide comprehensive health services to the community, both curative and rehabilitative, where hospital services reach family and environmental services. The aim of the study was to analyze the effect of the quality of health services on patient satisfaction in the inpatient room of the Medan Indonesian Workers' Imelda Hospital. The research design used in this study was an analytic survey with a cross sectional design. The population in this study were all patients who were treated from November 2022 to February 2023 in the Inpatient Room of the Imelda Indonesian Workers Hospital in Medan, totaling 167 people. The number of samples to be examined by the entire population is 62 people. Data analysis was performed using univariate, bivariate and multivariate analysis. The statistical test used is the chi square test and logistic regression. The results of the chi square test showed that there was an influence of 8 variables, namely technical competence, human relations, effectiveness, efficiency, continuity, security, human relations and convenience, which had a p-value <α 0.05, meaning technical competence, human relations, effectiveness, efficiency, continuity, security, human relations and comfort affect patient satisfaction in the inpatient room of Medan Indonesian Workers Imelda Hospital, and the multivariate test with the results of multiple logistic regression tests shows that the variable of technical competence is the most dominant with an odds ratio (OR) of 45,348 meaning 4 times affect patient satisfaction. The conclusion was that the dominant technical competency variable had the most influence on patient satisfaction in the inpatient room of Imelda Indonesian Workers Medan Hospital. It is recommended for the hospital to make policies in order to improve technical competence in the treatment room so as to produce optimal patient satisfaction..